A stereological study: Volume estimation in the cerebellum of Norduz sheep - Kiran, M; Cakmak, G (Journal of the Hellenic Veterinary Medical Society, 2024)
In this research, it was aimed to investigate the cerebellum volume values of Norduz sheep raised within the borders of Gurpinar district of Van province. For this purpose, 6 male and 6 female Norduz sheep heads were selected as materials. The brains were dissected and kept in formaldehyde for a week. Cerebellums were separated from the brain hemispheriums. For better fixation, the cerebellums were kept in formaldehyde again for a week. Tissues obtained by sequential random sampling were included in tissue tracking. Then each tissue was embedded in paraffin. An average of 10-12 sections with a thickness of 5µm were obtained from the tissue cassettes obtained by a Rotary microtome (Leica RM, 2135, Nussloch Germany). Sections stained with hematoxylin and eosin were photographed with an x4 objective. From these photographs, total cerebellum, medulla and cortex volumes, as well as vermis volume, were calculated using the Shtereom I program using the Cavalieri Principle. The results were evaluated statistically with the Mann-Whitney U test. No statistical difference was detected in terms of male and female cerebellum volume values, Coefficient of Error (CE) and Noise calculations (p>0.05). However, in the evaluation between genders, it was determined that the only difference was seen in the medulla section of the hemispherium cerebelli sinister (p<0.05). Keywords: Cavalieri Principle; cerebellum; Norduz sheep; stereology; volume.